Effect of Delignification Process on Cellulose, Hemicellulose, and Lignin Content on Liquid Glucose Production from a Mixture of Corn Cobs (Zea mays) and Sugar Cane Bagasse (Saccharum officinarum) - Hasani, Muhammad Aqil; Siswanto, Anggun Puspitarini (Program studi Teknik Kimia UNS, 2023)
ABSTRACT. Dependence on the use of fossil energy is continuously increasing every year. This is very risky, considering the dwindling availability of fossils in nature. It is necessary to use alternative energy as a substitute for fossil energy, such as bioethanol, one of the biofuels sourced from living things, especially plants. Bioethanol is based on the fermentation of glucose with bacteria that produce ethanol. Some essential ingredients for making bioethanol require a hydrolysis process to produce glucose so it can be fermented into bioethanol. This research focuses on the hydrolysis process to produce liquid glucose from a mixture of corn cobs and bagasse with several different treatments to determine glucose levels, cellulose, hemicellulose, and lignin levels. On the cellulose content itself, in the delignification process, the cellulose content obtained was 64.8% which was 11.1% higher than not through the delignification process, which was only 53.7%. The level of lignin is the same, the delignification process reduces the lignin content by 10% by not going through the delignification process by 21.3% compared to those undergoing the delignification process by only 10.3%. Hemicellulose is the same, with a 2% difference.Keywords: Corn Cob, Glucose, Hydrolysis, Sugarcane Bagasse